Book Translations as Idea Flows: The Effects of the Collapse of Communism on the Diffusion of Knowledge. Issue 6 (1st December 2014) - Abramitzky, Ran; Sin, Isabelle
Abstract: We use book translations as a new measure of international idea flows and study the effects of Communism's collapse in Eastern Europe on these flows. Using novel data on 800, 000 translations and difference-in-differences approaches, we show that while translations between Communist languages decreased by two thirds with the collapse, Western-to-Communist translations increased by a factor of 4 and quickly converged to Western levels. Convergence was more pronounced in the fields of applied and social sciences, and was more complete in Satellite and Baltic than in Soviet countries. We discuss how these patterns help us understand how repressive institutions and preferences towards Western European ideas shaped the international diffusion of knowledge.